Students’ Knowledge on Past Tense snd Their Ability to Write Narrative Text - Moh Hanafi (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
This researched was aimed at investigating the correlation between students’ mastery on grammar especially past tense and their ability to write narrative text. This researched used correlational research design with two instruments to take the data, that is, writing test and grammar test of past tense. The result of the data analysis showed that it was found that the coefficient of the correlation was .594. Therefore, the correlation can be interpreted as a positive medium correlation. It means the students who has higher knowledge on past tense, they can write better in writing narrative text. In the other hand, the hypothesis that the higher knowledge on past tense that the students have the better they can write narrative text was verified. It means the null hypothesis (Ho) rejected and alternative hypothesis (Ha)accepted. It can be concluded that there was a positive medium correlation between the students’ knowledge on past tense